Autism and Vitamin D - Khaled Saad; Abdulrahman A Al-Atram (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2017)
Autism spectrum disorder (ASD) is a complex neurodevelopmental syndrome. It begins before three years of age. ASD is characterized by pervasive deficits in social interaction, impairment in verbal and nonverbal communication, and stereotyped patterns of interests and activities. The increasing incidence of ASD in the pediatric population and the lack of successful curative therapies make ASD one of the most challenging disorders for medicine [1,2]. The pathogenesis of ASD is bewildering. The chemosensory immune system participates in neuro development, regulating neuronal proliferation, synapse formation and plasticity, along with removing apoptotic neurons [3]. Hundreds of studies over the last 4 decades have reported altered immune responses in autistic individuals. We found significant inverse relationships between serum 25-OH vitamin D levels and the frequencies of dendritic cells (DCs) population in children with ASD [1]. Vitamin D has an important role in brain homeostasis, neuro development, ageing, and significantly, in gene regulation. Also, it has been shown to bind to more than 2700 genes and to regulate the expression of more than 200 of them [2,4-6]. Many studies suggested that vitamin D has an important role as a neuroactive steroid, which can affect neuronal differentiation, axonal connectivity and brain structure and function.